Leading World Class Indonesian Islamic University: A Perspective of International Quality Assurance System - Thoyib, Muhammad; Ahmadi, Ahmadi; Humaisi, M. Syafiq; Nurdin, Muhamad; Djuhan, Widda; Wan Hasan, Wan Norhaniza (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
ABSTRACT. This article aims to explain the urgency of implementing AUN-QA and FIBAA as an international standard quality assurance system for world class universities implemented in the Indonesian Islamic Higher Education (IIHE), as well as an answer in responding to the demands of global education competition. This article is a qualitative research with a case type, where the data analysis technique used is the Miles, Huberman, and Saldana interactive analysis model which emphasizes the integration of several stages, namely: data collection, data condensation, data presentation, and data verification. The results of this study confirm that: 1) The international standard quality assurance policy of AUN-QA and FIBAA at UII Yogyakarta uses a bottom-up approach by considering internal and external aspects of institutional values; 2) The stages of international standard quality assurance of AUN-QA and FIBAA at UII uses the POAC model. This model has various consequences, namely; rigid, dynamic, detailed, and accommodating, as well as efficient and effective; 3) The implications of the AUN-QA and FIBAA international standard quality assurance systems in developing world class Islamic higher education at UII are very diverse, including: strengthening institutional commitment and quality culture, developing study programs, international partnerships, and increasing international publication of scientific works by lecturers and students.